2007
DOI: 10.2217/14750708.4.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid for the treatment of diabetic foot infections

Abstract: The hemostatic safety of strontium ranelate in the elderly population with osteoporosis was shown over 2 months of treatment; however, its long-term hemostatic safety should be evaluated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Multiple studies suggested that individuals with a reduced or completely absent antiplatelet response to ASA might experience higher risks of vascular events. The cardiovascular risks were found to be higher in patients with ASA resistance when compared to those who had sufficient responses to ASA [1,2,3,4]. There are some data suggesting an association between severity and frequency of acute vascular events and poor platelet response after ASA in patients with coronary artery disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies suggested that individuals with a reduced or completely absent antiplatelet response to ASA might experience higher risks of vascular events. The cardiovascular risks were found to be higher in patients with ASA resistance when compared to those who had sufficient responses to ASA [1,2,3,4]. There are some data suggesting an association between severity and frequency of acute vascular events and poor platelet response after ASA in patients with coronary artery disease [5].…”
Section: Introductionmentioning
confidence: 99%